Polydatin ameliorates hyperhidrosis by targeting Aqp5 in a mouse model - Chen, Jian-Feng; Feng, Zhi; Yu, Feng-Qiang; Qiu, Rui-Qin; Li, Xu; Lin, Jian-Bo (Frontiers in Pharmacology, 2025)
BackgroundPrimary focal hyperhidrosis (PFH) is a neurological dermatological disorder characterized by localized, excessive sweating. Current treatments have limitations, and postoperative compensatory hyperhidrosis remains a concern. Aquaporin 5 (AQP5) and neurologic factors such as Brain-Derived Neurotrophic Factor (BDNF) and Neuregulin-1 (NRG-1) are known to play key roles in sweat regulation. Polydatin, a natural compound with anti-inflammatory and neuroregulatory properties, has shown therapeutic potential in related conditions.MethodsThis preclinical experimental study investigated the effects of Polydatin in a mouse model of hyperhidrosis. Mice were treated with different doses and durations of Polydatin. Aqp5 knockout mice were used to explore the AQP5-related pathway. Sweat gland function, gene and protein expression (AQP5, BDNF, NRG-1), and cell responses to acetylcholine stimulation were analyzed.ResultsPolydatin at 50 mg/kg/day significantly reduced sweat secretion in hyperhidrotic mice (p < 0.001), while treatment duration showed no significant impact. The therapeutic effect was absent in Aqp5 knockout mice, confirming AQP5 dependence. Polydatin downregulated mRNA and protein expression of AQP5, Na+-K+-Cl- Cotransporter 1 (NKCC1), BDNF, and NRG-1. Additionally, Polydatin inhibited acetylcholine-induced proliferation of sweat gland cells (p < 0.05), an effect abolished by Aqp5 knockdown.ConclusionPolydatin alleviates hyperhidrosis by targeting AQP5 and suppressing key neurologic factors, supporting its potential as a novel therapeutic approach for PFH.